Revealing Human Motivation in the ‘Married Story’ by Noah Baumbach - Destiara, Radika Ayu; Atrinawati (Politeknik Negeri Sriwijaya, 2025)
This study explores the internal and external conflicts experienced by the married couple in Noah Baumbach’s 2009 film Marriage Story. The research examines how these conflicts unfold within the narrative and how they affect the characters’ relationship and family dynamics. Data for this study were obtained through library research and documentation methods, allowing for a comprehensive review of both primary and secondary sources related to the film. The analysis focuses on both intrinsic and extrinsic elements, employing textual, contextual, and qualitative approaches based on the theoretical frameworks of Kenney (1996) and Bernhardt (1953). These approaches are used to interpret the character development and the thematic portrayal of marital struggle. The findings reveal that the couple's conflicts are not merely circumstantial but are deeply rooted in the individual behaviours, personalities, and emotional responses of each character. Ultimately, the study highlights how personal flaws and miscommunication contribute significantly to the deterioration of their marriage and the emotional impact it has on their family unit. Keywords: internal conflicts, external conflicts, human motivation